Construction of free g-dimonoids - Movsisyan, Yu.; Davidov, S.; Safaryan, M. (Algebra and Discrete Mathematics, 2014)
In this paper, the concept of a g-dimonoid is introduced and the construction of a free g-dimonoid is described. (A g-dimonoid is a duplex satisfying two additional identities.)